Evaluation of Insecticide Strategies for Gall Midge and Yellow Stem Borer Management in Rice in Coastal Andhra Pradesh, India - P. Udayababu; K. Madhu Kumar; M Srinivasa Rao; G Sreenivas; P. V. Satyanarayana; D Manoj Kumar (Archives of Current Research International, 2025)
Efficient pest control in rice cultivation plays a vital role in sustaining crop yields and minimizing financial losses in agriculture. In recent times, delayed transplanting has led to a gradual increase in gall midge infestations, particularly in specific areas of Andhra Pradesh. Therefore, it is essential to assess the performance of various insecticides for managing gall midge outbreaks in rice crops. This research was conducted during the Kharif 2023 and Rabi 2023-24 seasons at the Agricultural Research Station in Ragolu, situated in the North Coastal Zone of Andhra Pradesh, with the objective of examining the efficacy of selected insecticides and their combinations against major insect pests in rice. The study comprised nine treatments viz., T1 – Carbofuran 3% CG at 10 kg/acre, T2 – Fipronil 0.3 GR at 10 kg/acre, T3 – Chlorpyriphos granules at 4 kg/acre, T4 – Chlorpyriphos 20 EC at 2.5 ml/litre, T5 Fipronil 5 SC at 2 ml/litre, T6 – Chlorantraniliprole 0.4 GR at 4 kg/acre, T7 – Chlorantraniliprole 18.5% SC at 0.3 ml/litre, T8 – Cartap hydrochloride 4% GR at 7.5 kg/acre, T9 – Untreated control. The goal was to optimize insecticide usage, avoiding redundant soil applications and foliar sprays, thereby reducing pest management costs for farmers. Among the tested options, fipronil 0.3 GR (T2) applied in the main field proved to be the most effective against gall midge, showing a significant reduction in silver shoot incidence when compared to other treatments. It was followed by carbofuran 3% CG (T1) and fipronil 5 SC (T5). For yellow stem borer control, chlorantraniliprole 0.4 GR (T6) showed the best performance in minimizing the occurrence of dead hearts and white ear symptoms, with chlorantraniliprole (T7) and cartap hydrochloride (T8) also showing positive effects. All treated plots recorded higher grain yields compared to the untreated control, with the highest yield observed in plots treated with fipronil 0.3 GR (T2) at 10 and 30 days after transplanting, followed by carbofuran application.